2015
DOI: 10.1165/rcmb.2015-0038oc
|View full text |Cite
|
Sign up to set email alerts
|

IL-17RA Signaling in Airway Inflammation and Bronchial Hyperreactivity in Allergic Asthma

Abstract: Asthma is a heterogeneous disease characterized by airway inflammation and hyperreactivity. IL-17 receptor A (IL-17RA) is a shared receptor subunit required for activity of IL-17 family cytokines, including IL-17A and IL-25. IL-17A and IL-25 induce different proinflammatory responses, and concentrations are elevated in subjects with asthma. However, the individual contributions of IL-17A and IL-25 to disease pathogenesis are unclear. We explored proinflammatory activities of the IL-17 pathway in models of pulm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
46
2
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 48 publications
1
46
2
2
Order By: Relevance
“…The Amgen cDNA libraries were prepared from total RNA isolated using Mirvana miRNA isolation kits (Ambion, Grand Island, NY) with on-colum DNase treatment as described previously60. Total RNA quality and concentration was determined using Bioanalzyer (Agilent, Santa Clara, CA) and NanoDrop (ThermoScientific, Wilmington, DE) instruments.…”
Section: Methodsmentioning
confidence: 99%
“…The Amgen cDNA libraries were prepared from total RNA isolated using Mirvana miRNA isolation kits (Ambion, Grand Island, NY) with on-colum DNase treatment as described previously60. Total RNA quality and concentration was determined using Bioanalzyer (Agilent, Santa Clara, CA) and NanoDrop (ThermoScientific, Wilmington, DE) instruments.…”
Section: Methodsmentioning
confidence: 99%
“…[5][6][7] Increased levels of IL-17 in bronchoalveolar lavage fluid (BALF), blood and sputum of patients with allergic asthma have been reported. 8 Sequencing studies revealed that IL-17 activates stromal cells to release chemokines and cytokines and increases the expression of extracellular matrix proteins in allergic asthma. 9,10 In addition, IL-17 enhances eosinophilic recruitment during airway inflammation in allergic asthma.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, IL-17A may also be involved in airway remodeling. IL-17A has been reported to increase airway smooth muscle contraction on methacholine stimulation and drive migration of airway smooth muscle cells in murine models of allergic inflammation and in patients with asthma 9, 14, 15. IL-17A binds to the receptor subunits IL-17RA and C, which are expressed on epithelial and mesenchymal cells as well as on some immune cell populations such as lymphocytes, dendritic cells, and monocytes/macrophages in the lung 16 .…”
mentioning
confidence: 99%
“…Mice that lack IL-17RA produce less CXCL1 and CXCL2 on pulmonary challenge with Klebsiella pneumoniae 17 and IL-17RA signaling is also necessary for host defense against Candida albicans 18 . In 2 mouse models, blocking IL-17R and IL-17RB reduced airway inflammation and airway hyperreactivity 14 . T H 17 cells also secrete IL-22, and IL-22 mRNA is elevated in PBMCs in pediatric patients with severe asthma, and rhinitis 19 .…”
mentioning
confidence: 99%